2017
DOI: 10.1103/physrevb.96.214511
|View full text |Cite
|
Sign up to set email alerts
|

Three-qubit direct dispersive parity measurement with tunable coupling qubits

Abstract: We consider the direct three-qubit parity measurement scheme with two measurement resonators, using circuit quantum electrodynamics to analyze its functioning for several different types of superconducting qubits. We find that for the most common, transmon-like qubit, the presence of additional qubit-state-dependent coupling terms of the two resonators hinders the possibility of performing the direct parity measurement. We show how this problem can be solved by employing the tunable coupling qubit (TCQ) in a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As such, we have ignored other sources of infidelity, particularly dephasing of the parity subspaces due to imperfect overlap of the entangled microwave fields, which is analogous to ignoring entangling gate infidelity in analyses of ancilla-based error correction. Some analysis of these types of implementation imperfections has begun in recent years [58][59][60][61], but more investigation is needed for a definitive assessment. Second, while we have presented a practical method for directly measuring the ZZ parities needed for bit-flip correction, we have not addressed how to directly measure the XX parities needed for additional phase-flip correction.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we have ignored other sources of infidelity, particularly dephasing of the parity subspaces due to imperfect overlap of the entangled microwave fields, which is analogous to ignoring entangling gate infidelity in analyses of ancilla-based error correction. Some analysis of these types of implementation imperfections has begun in recent years [58][59][60][61], but more investigation is needed for a definitive assessment. Second, while we have presented a practical method for directly measuring the ZZ parities needed for bit-flip correction, we have not addressed how to directly measure the XX parities needed for additional phase-flip correction.…”
Section: Discussionmentioning
confidence: 99%
“…The picture changes qualitatively if entanglement is instead generated using native two-body measurements -a context for which this code is optimized [1]. Direct two-body measurements have been proposed and demonstrated experimentally in circuit QED [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and are expected to be the native operation in Majorana-based architectures [1,14,32]. In this setting, we observe a honeycomb code threshold between 1.5% and 2.0% -by comparison, previous work reported a surface code threshold of 0.237% in the same error model [14] (but using a less accurate union-find decoder).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…This can to some extent already be achieved with a small atom, whose single coupling point can be at a node for some modes and at an antinode for others. However, we note that a recent theory proposal (Ciani and DiVincenzo 2017) uses a superconducting qubit with tunable coupling connected at multiple points to two resonators to cancel certain unwanted interaction terms while keeping desired interaction terms; it is shown that this would not have been possible with a small atom.…”
Section: Coupling a Giant Atom To A Cavitymentioning
confidence: 92%